Efektivitas Layanan Cendikia Berbasis E-Government dalam Percepatan Penerbitan Dokumen KIA (Kartu Identitas Anak) di Kota Pekanbaru - Maria Ulfa; Febri Yuliani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Pekanbaru City Population and Civil Registration Service has issued an e-government-based service, namely an application-shaped platform to help facilitate the issuance of children's identity documents, called the Cendikia service, which can be accessed via the web on the pekanbaru.go.id/kia page, where the public can submit requests for services. issuing child identity cards online without having to come and queue at the Pekanbaru City Population and Civil Registration Office. In implementing this service, there are still people who do not realize the importance of making KIA, there are overlapping applications in submitting KIA, people who do not understand how to use the Cendikia service, and there is a lack of direct socialization regarding the web-based Cendikia application service. This research aims to determine the effectiveness of Cendikia's services in accelerating the issuance of KIA documents. The theory used is Campbell's (1989) effectiveness theory in Mutiarin and Zainuddin (2014) with 5 (five) indicators, namely Program Success, Target Success, Program Satisfaction, Input and Output Levels, and Overall Goal Achievement. This research uses qualitative methods with data collection techniques obtained through observation, interviews and documentation. The results of this research show that the creation of Child Identity Cards in the Cendikia service has not been effective as seen from the indicators of the level of program success and target success, the Cendikia service still has several factors which are obstacles found in the system (internal) and outside the system (external). thus causing the implementation of these services to be ineffective.